2008
DOI: 10.1121/1.2967890
|View full text |Cite
|
Sign up to set email alerts
|

The influence of noise exposure on the parameters of a convolution model of the compound action potential

Abstract: The influence of noise exposure on the parameters of a convolution model of the compound action potential ͑CAP͒ was examined. CAPs were recorded in normal-hearing gerbils and in gerbils exposed to a 117 dB SPL 8 kHz band of noise for various durations. The CAPs were fitted with an analytic CAP to obtain the parameters representing the number of nerve fibers ͑N͒, the probability density function ͓P͑t͔͒ from a population of nerve fibers, and the single-unit waveform ͓U͑t͔͒. The results showed that the analytic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Latency reductions are probably due to the particular mammalian cochlea mechanical tonotopy and tuning properties. Increasing probe SPLs to elicit a response in a tonotopic region with trauma-induced threshold shift may activate fibers with a much higher center frequency, which are more basal in the cochlea and have a smaller traveling wave delay and shorter latency (11,36). Basilar membrane mechanical property changes from OHC damage are also implicated in latency reduction (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latency reductions are probably due to the particular mammalian cochlea mechanical tonotopy and tuning properties. Increasing probe SPLs to elicit a response in a tonotopic region with trauma-induced threshold shift may activate fibers with a much higher center frequency, which are more basal in the cochlea and have a smaller traveling wave delay and shorter latency (11,36). Basilar membrane mechanical property changes from OHC damage are also implicated in latency reduction (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…It is currently thought that reduced CAP after intense sound trauma is caused by reduced AN fiber recruitment (resulting from damage or death of hair cells and/or spiral ganglion neurons) and from a "broadening" of the response from desynchronization of afferents with similar center frequencies (11,36). Also, hair cells or AN fiber death or degeneration may occur over days to months (6,9).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1A presents an example of the high correlations achieved by Chertoff (2004) and in the current study between the analytic CAPs (gray line) and actual CAPs elicited from normal ears (black line). Chertoff et al (2008) showed that the analytic CAP could also reliably model CAPs recorded from animals after noise exposure. Lichtenhan and Chertoff (2008) extended the use of the convolution model to CAPs recorded with a custom tympanic membrane electrode (Ferraro & Durrant 2002) from human subjects with temporary noise-induced hearing threshold shifts.…”
Section: Introductionmentioning
confidence: 98%
“…Mills (2006) suggested that the combined use of auditory brain stem response (ABR) thresholds and distortion-product otoacoustic emission (DPOAE) amplitudes could differentiate between hearing loss related to stria vascularis damage and noise-induced hearing loss in an animal model. Chertoff (2004), Chertoff et al (2008), and Lichtenhan and Chertoff (2008) investigated the utility of the compound action potential (CAP) in identifying auditory nerve fiber degeneration associated with sensorineural hearing loss. Their approach was to characterize CAP morphology using Goldstein and Kiang's (1958) mathematical model given as,…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in the cochlear implant literature have indicated that the amplitude of electrically evoked auditory potentials is positively correlated with the number of viable auditory neurons (Smith and Simmons, 1983;Hall, 1990) and may gauge prognoses for implant recipients (Gibson and Sanli, 2007;Teagle et al, 2010). Chertoff (2004) and Chertoff et al (2008) used a gerbil model to determine the utility of the compound action potential (CAP) for quantifying auditory nerve pathology. Their approach was to analyze the morphology of CAPs by fitting the waveforms with a five-parameter convolution model adapted from Goldstein and Kiang's (1958) description of the CAP as the sum of synchronously firing auditory neurons.…”
Section: Introductionmentioning
confidence: 99%